The Protection of the Rights of the Defendant by the Constitutional Court-The Kosovo Case - Adelina Rakaj (Faculty of Law, Andalas University, 2020)
The aim of this case study is to analyze the protection of the rights of the defendant in criminal proceedings and the implementation of international standards on the rights of the defendant in criminal proceedings in the domestic law of the Republic of Kosovo. This paper will focus on the role of the Constitutional Court of Kosovo in protecting the rights of the defendant during a criminal process, based on specific cases decided by the Constitutional Court of the Republic of Kosovo. For more than ten years since the Declaration of its Independence, Kosovo has established a legal system, which provides effective protection for the rights of a defendant. A significant role in this regard was played by the fact that Kosovo directly applies the jurisprudence of the International Court on Human Rights (ECtHR), as a constitutional obligation. Out of all institutions of the legal system in Kosovo, which are obliged to protect the rights of defendants, a determinant role was played by the Constitutional Court in such regards, therefore, this paper presents arguments how the Constitutional Court of Kosovo has become a guardian for protection of the rights of defendants, in compliance with the Jurisprudence of the ECtHR